-5x(-6x-x)=6+3(8+2x)

Simple and best practice solution for -5x(-6x-x)=6+3(8+2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x(-6x-x)=6+3(8+2x) equation:


Simplifying
-5x(-6x + -1x) = 6 + 3(8 + 2x)

Combine like terms: -6x + -1x = -7x
-5x(-7x) = 6 + 3(8 + 2x)

Remove parenthesis around (-7x)
-5x * -7x = 6 + 3(8 + 2x)

Reorder the terms for easier multiplication:
-5 * -7x * x = 6 + 3(8 + 2x)

Multiply -5 * -7
35x * x = 6 + 3(8 + 2x)

Multiply x * x
35x2 = 6 + 3(8 + 2x)
35x2 = 6 + (8 * 3 + 2x * 3)
35x2 = 6 + (24 + 6x)

Combine like terms: 6 + 24 = 30
35x2 = 30 + 6x

Solving
35x2 = 30 + 6x

Solving for variable 'x'.

Reorder the terms:
-30 + -6x + 35x2 = 30 + 6x + -30 + -6x

Reorder the terms:
-30 + -6x + 35x2 = 30 + -30 + 6x + -6x

Combine like terms: 30 + -30 = 0
-30 + -6x + 35x2 = 0 + 6x + -6x
-30 + -6x + 35x2 = 6x + -6x

Combine like terms: 6x + -6x = 0
-30 + -6x + 35x2 = 0

Begin completing the square.  Divide all terms by
35 the coefficient of the squared term: 

Divide each side by '35'.
-0.8571428571 + -0.1714285714x + x2 = 0

Move the constant term to the right:

Add '0.8571428571' to each side of the equation.
-0.8571428571 + -0.1714285714x + 0.8571428571 + x2 = 0 + 0.8571428571

Reorder the terms:
-0.8571428571 + 0.8571428571 + -0.1714285714x + x2 = 0 + 0.8571428571

Combine like terms: -0.8571428571 + 0.8571428571 = 0.0000000000
0.0000000000 + -0.1714285714x + x2 = 0 + 0.8571428571
-0.1714285714x + x2 = 0 + 0.8571428571

Combine like terms: 0 + 0.8571428571 = 0.8571428571
-0.1714285714x + x2 = 0.8571428571

The x term is -0.1714285714x.  Take half its coefficient (-0.0857142857).
Square it (0.007346938773) and add it to both sides.

Add '0.007346938773' to each side of the equation.
-0.1714285714x + 0.007346938773 + x2 = 0.8571428571 + 0.007346938773

Reorder the terms:
0.007346938773 + -0.1714285714x + x2 = 0.8571428571 + 0.007346938773

Combine like terms: 0.8571428571 + 0.007346938773 = 0.864489795873
0.007346938773 + -0.1714285714x + x2 = 0.864489795873

Factor a perfect square on the left side:
(x + -0.0857142857)(x + -0.0857142857) = 0.864489795873

Calculate the square root of the right side: 0.929779434

Break this problem into two subproblems by setting 
(x + -0.0857142857) equal to 0.929779434 and -0.929779434.

Subproblem 1

x + -0.0857142857 = 0.929779434 Simplifying x + -0.0857142857 = 0.929779434 Reorder the terms: -0.0857142857 + x = 0.929779434 Solving -0.0857142857 + x = 0.929779434 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.0857142857' to each side of the equation. -0.0857142857 + 0.0857142857 + x = 0.929779434 + 0.0857142857 Combine like terms: -0.0857142857 + 0.0857142857 = 0.0000000000 0.0000000000 + x = 0.929779434 + 0.0857142857 x = 0.929779434 + 0.0857142857 Combine like terms: 0.929779434 + 0.0857142857 = 1.0154937197 x = 1.0154937197 Simplifying x = 1.0154937197

Subproblem 2

x + -0.0857142857 = -0.929779434 Simplifying x + -0.0857142857 = -0.929779434 Reorder the terms: -0.0857142857 + x = -0.929779434 Solving -0.0857142857 + x = -0.929779434 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.0857142857' to each side of the equation. -0.0857142857 + 0.0857142857 + x = -0.929779434 + 0.0857142857 Combine like terms: -0.0857142857 + 0.0857142857 = 0.0000000000 0.0000000000 + x = -0.929779434 + 0.0857142857 x = -0.929779434 + 0.0857142857 Combine like terms: -0.929779434 + 0.0857142857 = -0.8440651483 x = -0.8440651483 Simplifying x = -0.8440651483

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.0154937197, -0.8440651483}

See similar equations:

| 7x-220=4x+80 | | 7.2x-3.8=2.2x+4 | | r=-40x-11+1990 | | 16y=15(y+9) | | 7r-5r+2=5r+2 | | 3(2x+5)+6(x+2)= | | 2y=3y-2 | | y=2x^2+5x+1 | | -12x^2+8x+15=0 | | X-7=-5+7 | | [4x+2]=10 | | 5(4x+5)=75 | | 5x-2+4x=7 | | -7=2+x | | 3.14=6x-5y | | 12x-40=120+5x | | (x+8)3=66 | | -3+5(x+6)=27 | | 6x-4=2(3x+6) | | 4(x)-9=75 | | X+50=4x | | X+5x=4x | | 100x-10x=10 | | 500+ap=5000 | | 4d+3=-16d | | 4-2b=19 | | 5x-4x+3=x | | 747-60x=300 | | 5(z+2)=25 | | 7-3x=y | | 2345x-23167=3 | | 747-60x=147 |

Equations solver categories